High-impermeability curing agent for sandy soil and preparation method of high-impermeability curing agent

Through a high anti-seepage curing agent combined with solid waste-based sulfur aluminum-ferrous aluminum-type gelling material and slag powder, a crystal-colloid composite hydration product system is formed, which solves the problem of insufficient anti-seepage performance of sandy soil and achieves efficient sand Soil solidification and solid waste resource utilization reduce environmental impact and production costs.

CN119241186AActive Publication Date: 2025-01-03SHANDONG UNIV

Patent Information

Application Number
CN202411602096.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-03
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively improve the permeability of sandy soil. Commonly used cured materials such as silicate cement and alkali excitation materials have insufficient performance improvement, and production energy consumption and carbon emissions are large, and sulfur aluminate cement is insufficient. Influence mechanical properties.

Method used

The combination of solid waste-based sulfur-ferrous aluminum-type gelling materials, slag powder, ordinary silicate cement, desulfurization gypsum and silica fume is used to form the ettringite skeleton structure and C-(A)-S-H gel through early hydration. Provide cementation, form a crystal-colloid composite hydration product system, improve the permeability and mechanical properties of sand and soil, and realize the comprehensive utilization of solid waste.

Benefits of technology

It significantly improves the compressive, flexural strength and permeability of sand and soil, achieves rapid curing and resource utilization, reduces the cost and environmental impact of solid waste accumulation, and is relatively low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241186A_ABST
    Figure CN119241186A_ABST
Patent Text Reader

Abstract

The invention discloses a high-impermeability curing agent for sandy soil and a preparation method, the high-impermeability curing agent comprises the following components by mass: 30-50 parts of a solid waste-based sulfur aluminum iron series cementing material; 10 to 30 parts of slag powder; 5-30 parts of ordinary Portland cement; 5-20 parts of desulfurized gypsum; and 1-10 parts of silica fume. A curing agent system further strengthens the hydration effect and the cementing performance of the cementing material, and a formed crystal-colloid composite hydration product system contributes to the stable and compact microstructure of the cured sandy soil, so that the impermeability and the mechanical property of the sandy soil can be greatly improved; the comprehensive application of solid waste raw materials such as desulfurized gypsum and mineral powder is realized, and the stacking cost of solid wastes and the influence on the environment are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of curing agents, and in particular relates to a high-impermeability curing agent for sandy soil and a preparation method thereof. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] Sandy soil has high permeability. Under the influence of rainfall erosion, surface runoff erosion, etc., water can easily enter the structure of sandy soil buildings, leading to severe problems such as cracking and collapse, which have a serious impact on engineering construction and the safety of people's lives and property. Therefore, high-impermeability solidification of sandy soil should be carried out to realize its resource utilization. However, the high-impermeability solidification of sandy soil is currently a major technical problem, and it is difficult for ordinary solidification materials to achieve a good anti-permeability solidification effect on sandy soil.

[0004] For example, the commonly used solidifying material silicate cement is difficult to fill the pores of sand, which leads to limited improvement in the impermeability of the solidified soil, and has disadvantages such as high production energy consumption and carbon emissions; alkali-activated materials often use activated materials such as water glass, which lack uniformity and often require more than 28 days of curing time to achieve a good effect of improving impermeability; the fiber-like structure of calcium sulfoxide, the hydration product of sulphoaluminate cement, can form a network structure in the soil, play a skeleton support role and fill the loose soil structure, which can improve the early strength and impermeability of the soil, and is especially suitable for high impermeability solidification of sandy soil, but its cementing property is not enough to bond sand particles, resulting in the degree to which sulphoaluminate cement improves the mechanical properties and impermeability of solidified sand, and it should be compositely optimized. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention aims to provide a high impermeability curing agent for sandy soil and a preparation method thereof.

[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0007] In a first aspect, the present invention provides a high impermeability curing agent for sandy soil, which is composed of the following components, by mass: 30-50 parts of solid waste-based sulfur-aluminum-iron cementitious material; 10-30 parts of slag powder; 5-30 parts of ordinary Portland cement; 5-20 parts of desulfurized gypsum; and 1-10 parts of silica fume.

[0008] Solid waste-based sulfur-aluminum-iron cementitious materials: rapid hydration in the early stage provides ettringite, which provides early strength; ettringite is a short rod-shaped crystal that overlaps each other in the solidified soil to form a skeleton structure, providing stability.

[0009] Slag powder: It has volcanic ash activity. The Si and Al phases in its chemical composition can be excited in an alkaline environment and react with OH - The generated C-(A)-SH gel provides a cementing effect for the solidified soil system and connects the dispersed soil particles into a whole.

[0010] Ordinary Portland cement: It hydrates itself to form CSH gel. The generated Ca(OH)2 can provide sufficient OH- for the system and promote the excitation effect of mineral powder.

[0011] Desulfurized gypsum: Its component is CaSO4, which stabilizes the morphology of calcium sulfoaluminate and reduces the presence of monosulfide hydrated calcium sulfoaluminate in the system.

[0012] Silica fume: It has volcanic ash activity. The Si phase in its chemical composition can be stimulated to form CSH gel in an alkaline environment.

[0013] By taking advantage of the early strength and impermeability characteristics of solid waste-based sulfoaluminum-iron cementitious materials, slag, ordinary Portland cement, desulfurized gypsum, silica fume, etc. are compounded to enrich the types of hydration products, providing a "skeleton-filling-cementation" effect for sand. On the basis of the hydration of sulfoaluminum-iron cementitious materials to form calcium aluminate crystals, colloidal products are supplemented, so that soil, particles and hydration products form an effective connection, which not only further strengthens the hydration and cementation properties of the cementitious materials, but also the formed crystal-colloidal composite hydration product system will contribute to the stability and dense microstructure of the solidified sand, which can effectively improve the impermeability and mechanical properties of the sand, realize the resource utilization of the sand, and at the same time realize the comprehensive application of solid waste raw materials such as desulfurized gypsum and mineral powder, reducing the accumulation cost of solid waste and the impact on the environment.

[0014] In some embodiments, the preparation method of the solid waste-based sulfur-aluminum-iron cementitious material is as follows: 30-40 parts of desulfurized gypsum, 10-20 parts of red mud, 20-25 parts of aluminum ash and 20-30 parts of carbide slag are uniformly mixed, and the mixed raw materials are added into a kiln and calcined for 20-40 minutes at a temperature of 1150-1300° C. to obtain clinker;

[0015] 80 parts of clinker, 15 parts of desulfurized gypsum and 5 parts of limestone powder are dried and mixed to prepare a solid waste-based sulfur-aluminum-iron cementitious material.

[0016] The iron content of this solid waste-based sulfur-aluminum-iron cementitious material is about 8.35%. The iron phase can form iron glue when cement is hydrated to cement soil particles. The raw materials of this high-impermeability curing agent are all derived from solid waste, which is low-carbon and solves the problem of bulk solid waste disposal.

[0017] Preferably, when preparing the solid waste-based sulfur-aluminum-iron cementitious material, the raw materials are 35-40 parts of desulfurized gypsum, 15-20 parts of red mud, 20-25 parts of aluminum ash and 25-30 parts of carbide slag;

[0018] More preferably, the composition comprises 36 parts of desulfurized gypsum, 16 parts of red mud, 22 parts of aluminum ash and 26 parts of carbide slag.

[0019] In some embodiments, the high impermeability curing agent for sandy soil is composed of the following components, measured by mass: 30-40 parts of solid waste-based sulfur-aluminum-iron cementitious material; 20-30 parts of slag powder; 10-30 parts of ordinary Portland cement; 5-20 parts of desulfurized gypsum; and 4-10 parts of silica fume.

[0020] Preferably, the high impermeability curing agent for sandy soil is composed of the following components by mass: 30-35 parts of solid waste-based sulfur-aluminum-iron cementitious material; 20-25 parts of slag powder; 15-20 parts of ordinary Portland cement; 15-20 parts of desulfurized gypsum; and 4-7 parts of silica fume.

[0021] In some embodiments, in the high impermeability solidifying agent for sandy soil, each component is ground and the residue on a 200-mesh square sieve is less than 10%.

[0022] In a second aspect, the present invention provides a method for preparing the high impermeability curing agent for sandy soil, comprising the following steps:

[0023] Solid waste-based sulfur-aluminum-iron cementitious materials, slag powder, ordinary Portland cement, desulfurized gypsum and silica fume are weighed in proportion, ground to a size where the residue on a 200-mesh square sieve is less than 10%, and mixed to obtain the product.

[0024] In some embodiments, the method for modifying sandy soil using the high impermeability curing agent is: adjusting the moisture content of the sandy soil, mixing the high impermeability curing agent and the sandy soil in a mass ratio of 5-15:85-95 to obtain a mixed soil material; and preparing test pieces with the mixed soil material.

[0025] Preferably, when the sandy soil is modified, the water content of the sandy soil is 8%-20%.

[0026] Preferably, the mass ratio of the high impermeability curing agent to the sandy soil is 7-12:87-92, preferably 10:90.

[0027] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0028] The sulphur-aluminum-iron composite cementitious material suitable for high-anti-seepage solidification of sandy soil prepared by the present invention, in terms of raw material selection, makes use of the early strength and anti-seepage characteristics of solid waste-based sulphur-aluminum-iron composite cementitious materials, and compound slag, ordinary silicate cement, desulfurized gypsum, silica fume, etc., to enrich the types of its hydration products, provide a "skeleton-filling-cementation" effect for the sand, and supplement colloidal products on the basis of the hydration of the sulphur-aluminum-iron composite cementitious materials to form calcium aluminate crystals, so that the soil, particles, and hydration products form an effective connection, which not only further strengthens the hydration and cementation properties of the cementitious materials, but also the formed crystal-colloid composite hydration product system will contribute to the stability and dense microstructure of the solidified sand, which can effectively improve the anti-seepage and mechanical properties of the sand, realize the resource utilization of the sand, and at the same time realize the comprehensive application of solid waste raw materials such as desulfurized gypsum and mineral powder, reducing the accumulation cost of solid waste and the impact on the environment.

[0029] From the performance point of view, the high-impermeability curing agent of the present invention has good compressive and flexural strength and excellent mechanical properties. When this high-impermeability curing agent is used to solidify sandy soil, the anti-permeability coefficient of the sandy soil completely exceeds the engineering requirements of dam filling. This invention not only provides important technical guidance for the current sandy soil solidification problem, but also promotes the resource utilization of sandy soil and environmental sustainable development.

[0030] When the high anti-seepage curing agent of the present invention is used to solidify sand, the curing efficiency is high, relatively fast curing can be achieved, and the working efficiency is improved.

[0031] The prepared high-impermeability curing agent has the advantages of early strength, high strength, and stable strength improvement. It has greatly improved compressive and flexural strengths compared to ordinary sulphoaluminate cement and has superior mechanical properties.

[0032] The 7-day impermeability coefficient of sand solidified by the prepared high impermeability curing agent reached 5.9×10 -7 cm / s, meeting the quality technical indicators of general soil anti-seepage materials in relevant national regulations (≤1×10 -5 ), the performance is improved quickly and the effect is good.

[0033] The prepared high-impermeability curing agent replaces cementitious material clinker with multiple solid wastes (mineral powder, desulfurized gypsum), reducing the calcination cost. Compared with traditional sulphoaluminate cement, the cost is reduced by more than half.

[0034] The prepared high-impermeability curing agent uses a large amount of solid waste, which reduces the accumulation cost of solid waste and the impact on the environment, and reduces energy consumption and carbon emissions in the production process.

[0035] The preparation process is simple, and the modification method for sandy soil is simple. The prepared high-impermeability curing agent is simple to use mechanically, and the mechanical use difficulty is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0037] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0038] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0039] The present invention will be further described below in conjunction with the embodiments.

[0040] Example 1

[0041] A high-impermeability curing agent for sand solidification is composed of the following components in parts by mass: 35 parts of solid waste-based sulfur-aluminum-iron cementitious materials, 30 parts of slag powder, 15 parts of ordinary Portland cement, 5 parts of desulfurized gypsum, and 15 parts of silica fume.

[0042] The preparation method of the solid waste-based sulfur-aluminum-iron cementitious material is as follows: 36 parts of desulfurized gypsum, 16 parts of red mud, 22 parts of aluminum ash and 26 parts of carbide slag are mixed, and the mixed raw materials are added into a kiln and calcined for 30 minutes at a calcination temperature of 1250°C to obtain sulfur-aluminum clinker;

[0043] 80 parts of sulphur-aluminium clinker, 15 parts of desulphurised gypsum and 5 parts of limestone powder are dried and mixed to prepare a solid waste-based sulphur-aluminium-iron cementitious material.

[0044] The high impermeability curing agent is applied to curing sandy soil, including the following steps:

[0045] (1) 35 parts of solid waste-based sulfur-aluminum-iron cementitious material, 30 parts of slag powder, 15 parts of ordinary Portland cement, 5 parts of desulfurized gypsum, and 15 parts of silica fume are taken, and the powders are ground and premixed to obtain a composite cementitious material with a fineness requirement of less than 10% on a 200-mesh square hole sieve;

[0046] (2) Dry the sandy soil, pass it through a 2 mm sieve, add water to adjust the optimum moisture content of the sandy soil to 15%, mix well and seal for 24 hours for later use;

[0047] (3) The composite cementitious material in step (1) and 52.5 sulphoaluminate cement are mixed into mortar at a water-cement ratio of 0.45 according to the national standard GB / T17671-2021 "Test method for strength of cement mortar (ISO method)" to prepare a 40×40×160 mm mortar sample and test its compressive strength and flexural strength.

[0048] (4) Weigh 10 parts of the composite cementitious material in step (1) and 90 parts of the wet soil in step (2) by mass, mix and stir, first slowly stir for 120 seconds, then quickly stir for 3 minutes, to prepare a mixed soil material.

[0049] (5) According to the compaction degree of 100%, cylindrical specimens with a size of 50 mm × 50 mm were prepared by static pressing. After demolding, they were placed in a curing room and standard cured (temperature 20 ± 2 °C, humidity ≥ 95%) for 7 days, 28 days and 60 days, and the unconfined compressive strength test of the cured soil was carried out. The preparation of the specimens and the determination of the unconfined compressive strength were based on GB / T 50123-2019 "Standard for Geotechnical Test Methods".

[0050] (6) According to the compaction degree of 100%, cylindrical specimens with a size of 61.8 mm × 40 mm were prepared by static pressing. After demolding, they were placed in a curing room for standard curing (temperature 20 ± 2 °C, humidity ≥ 95%) for 7 days, 28 days and 60 days, and the cured soil permeability test was carried out. The preparation of the specimens and the determination of the impermeability performance were based on GB / T50123-2019 "Standard for Geotechnical Test Methods".

[0051] Table 1 Mechanical properties of curing agent

[0052]

[0053] Table 2 Unconfined compressive strength of solidified sand

[0054]

[0055] Table 3 Anti-seepage properties of solidified sand

[0056]

[0057] Example 2

[0058] A high-impermeability curing agent for sand solidification is composed of the following components in parts by mass: 40 parts of solid waste-based sulfur-aluminum-iron cementitious materials, 30 parts of slag powder, 15 parts of ordinary Portland cement, 5 parts of desulfurized gypsum, and 5 parts of silica fume.

[0059] Its application to stabilize sandy soil includes the following steps:

[0060] (1) 40 parts of solid waste-based sulfur-aluminum-iron cementitious material, 30 parts of slag powder, 15 parts of ordinary Portland cement, 10 parts of desulfurized gypsum, and 5 parts of silica fume are taken, and the powder is ground and premixed. The fineness requirement is that the residue on a 200-mesh square sieve is less than 10%. The preparation method of the solid waste-based sulfur-aluminum-iron cementitious material is the same as that in Example 1;

[0061] (2) Dry the sandy soil, pass it through a 2 mm sieve, add water to adjust the optimum moisture content of the sandy soil to 15%, mix evenly, and seal for 24 hours for later use;

[0062] (3) The composite cementitious material and 52.5 sulphoaluminate cement in step (1) are mixed with mortar at a water-cement ratio of 0.45 according to the national standard GB / T17671-2021 "Test method for strength of cement mortar (ISO method)" to prepare a 40×40×160 mm mortar sample and test its compressive strength and flexural strength.

[0063] (4) Take 10 parts of the composite cementitious material in step (1) and 90 parts of the wet soil in step (2) by mass, mix and stir, first slowly stir for 120 seconds, then quickly stir for 3 minutes, to make a mixed soil material.

[0064] (5) According to the compaction degree of 100%, cylindrical specimens with a size of 50 mm × 50 mm were prepared by static pressing. After demolding, they were placed in a curing room and standard cured (temperature 20 ± 2 °C, humidity ≥ 95%) for 7 days, 28 days and 60 days, and the unconfined compressive strength test of the cured soil was carried out. The preparation of the specimens and the determination of the unconfined compressive strength were based on GB / T 50123-2019 "Standard for Geotechnical Test Methods".

[0065] (6) According to the compaction degree of 100%, cylindrical specimens with a size of 61.8 mm × 40 mm were prepared by static pressing. After demolding, they were placed in a curing room for standard curing (temperature 20 ± 2 °C, humidity ≥ 95%) for 7 days, 28 days and 60 days, and the cured soil permeability test was carried out. The preparation of the specimens and the determination of the impermeability performance were based on GB / T50123-2019 "Standard for Geotechnical Test Methods".

[0066] Table 4 Mechanical properties of curing agent

[0067]

[0068] Table 5 Unconfined compressive strength of solidified sand

[0069]

[0070] Table 6 Anti-seepage properties of solidified sand

[0071]

[0072] Example 3

[0073] A high-impermeability curing agent for sand solidification is composed of the following components in parts by mass: 30 parts of solid waste-based sulfur-aluminum-iron cementitious materials, 30 parts of slag powder, 15 parts of ordinary Portland cement, 15 parts of desulfurized gypsum, and 10 parts of silica fume.

[0074] Its application to stabilize sandy soil includes the following steps:

[0075] (1) Take 30 parts of solid waste-based sulfur-aluminum-iron cementitious material, 30 parts of slag powder, 15 parts of ordinary Portland cement, 15 parts of desulfurized gypsum, and 10 parts of silica fume, grind and premix them, and the fineness requirement is to meet the 200-mesh square hole sieve residue of less than 10%; the preparation method of solid waste-based sulfur-aluminum-iron cementitious material is the same as that of Example 1;

[0076] (2) Dry the sandy soil, pass it through a 2 mm sieve, add water to adjust it to the optimal moisture content of the sandy soil (15%), mix it evenly, and seal it for 24 hours for use;

[0077] (3) The composite cementitious material in step (1) and 52.5 sulphoaluminate cement are mixed with a water-cement ratio of 0.45 according to the national standard GB / T17671-2021 "Test method for strength of cement mortar (ISO method)" to prepare a 40×40×160 mm mortar sample and test its compressive strength and flexural strength.

[0078] (4) Take 10 parts of the composite cementitious material in step (1) and 90 parts of the wet soil in step (2) by mass, mix and stir, first slowly stir for 120 seconds, then quickly stir for 3 minutes, to prepare a mixed soil material.

[0079] (5) According to the compaction degree of 100%, cylindrical specimens with a size of 50 mm × 50 mm were prepared by static pressing. After demolding, they were placed in a curing room and standard cured (temperature 20 ± 2 °C, humidity ≥ 95%) for 7 days, 28 days and 60 days, and the unconfined compressive strength test of the cured soil was carried out. The preparation of the specimens and the determination of the unconfined compressive strength were based on GB / T 50123-2019 "Standard for Geotechnical Test Methods".

[0080] (6) According to the compaction degree of 100%, cylindrical specimens with a size of 61.8 mm × 40 mm were prepared by static pressing. After demolding, they were placed in the curing room and standard cured (temperature 20 ± 2 ° C, humidity ≥ 95%) for 7 days, 28 days and 60 days, and the cured soil permeability test was carried out. The preparation of the specimens and the determination of the impermeability performance were based on GB / T50123-2019 "Standard for Geotechnical Test Methods".

[0081] Table 7 Mechanical properties of curing agent

[0082]

[0083] Table 8 Unconfined compressive strength of solidified sand

[0084]

[0085] Table 9 Anti-seepage properties of solidified sand

[0086]

[0087] Comparative Example 1

[0088] The difference from Example 1 is:

[0089] (4) Weigh 10 parts of 52.5% sulphoaluminate cement and 90 parts of the wet soil in step (2) by mass, mix and stir, first slowly stir for 120 seconds and then quickly stir for 3 minutes to prepare a mixed soil material.

[0090] Table 10 Unconfined compressive strength of solidified sand

[0091]

[0092] Table 11 Anti-seepage properties of solidified sand

[0093]

[0094] Comparative Example 2

[0095] The difference from Example 1 is that 35 parts of solid waste-based sulfoaluminum-iron cementitious materials are replaced by 52.5 parts of sulfoaluminate cement, and the rest are the same as Example 1.

[0096] Table 12 Unconfined compressive strength of solidified sand

[0097]

[0098] Table 13 Anti-seepage properties of solidified sand

[0099]

[0100] Comparative Example 3

[0101] The difference from Example 1 is that 15 parts of silica fume are replaced by 15 parts of slag powder, and the rest is the same as Example 1.

[0102] Table 14 Unconfined compressive strength of solidified sand

[0103]

[0104] Table 15 Anti-seepage properties of solidified sand

[0105]

[0106] Comparative Example 4

[0107] The difference from Example 1 is that 15 parts of slag powder are replaced by 15 parts of silica fume, and the rest is the same as Example 1.

[0108] Table 16 Unconfined compressive strength of solidified sand

[0109]

[0110] Table 17 Anti-seepage properties of solidified sand

[0111]

[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high impermeability curing agent for sandy soil, characterized in that: The invention is composed of the following components by mass: 30-50 parts of solid waste-based sulfur-aluminum-iron cementitious materials; 10-30 parts of slag powder; 5-30 parts of ordinary Portland cement; 5-20 parts of desulfurized gypsum; and 1-10 parts of silica fume.

2. The high impermeability curing agent for sandy soil according to claim 1, characterized in that: The invention is composed of the following components by mass: 30-40 parts of solid waste-based sulfur-aluminum-iron cementitious materials; 20-30 parts of slag powder; 10-30 parts of ordinary Portland cement; 5-20 parts of desulfurized gypsum; and 4-10 parts of silica fume.

3. The high impermeability curing agent for sandy soil according to claim 2, characterized in that: The invention is composed of the following components by mass: 30-35 parts of solid waste-based sulfur-aluminum-iron cementitious materials; 20-25 parts of slag powder; 15-20 parts of ordinary Portland cement; 15-20 parts of desulfurized gypsum; and 4-7 parts of silica fume.

4. The high impermeability curing agent for sandy soil according to any one of claims 1 to 3, characterized in that: The preparation method of the solid waste-based sulfur-aluminum-iron cementitious material is as follows: 30-40 parts of desulfurized gypsum, 10-20 parts of red mud, 20-25 parts of aluminum ash and 20-30 parts of carbide slag are uniformly mixed, and the mixed raw materials are added into a kiln and calcined for 20-40 minutes at a temperature of 1150-1300° C. to obtain clinker; 80 parts of clinker, 15 parts of desulfurized gypsum and 5 parts of limestone powder are dried and mixed to prepare a solid waste-based sulfur-aluminum-iron cementitious material; Preferably, when preparing the solid waste-based sulfur-aluminum-iron cementitious material, the raw materials are 35-40 parts of desulfurized gypsum, 15-20 parts of red mud, 20-25 parts of aluminum ash and 25-30 parts of carbide slag; Preferred are: 36 parts of desulfurized gypsum, 16 parts of red mud, 22 parts of aluminum ash and 26 parts of carbide slag.

5. The high impermeability curing agent for sandy soil according to any one of claims 1 to 3, characterized in that: In the high-impermeability solidifying agent for sandy soil, each component is ground and the residue on a 200-mesh square sieve is less than 10%.

6. The method for preparing the high impermeability curing agent for sandy soil according to any one of claims 1 to 5, characterized in that: The steps include: Solid waste-based sulfur-aluminum-iron cementitious materials, slag powder, ordinary Portland cement, desulfurized gypsum and silica fume are weighed in proportion, ground to a size where the residue on a 200-mesh square sieve is less than 10%, and mixed to obtain the product.

7. The method for preparing a high impermeability curing agent for sandy soil according to claim 6, characterized in that: The method for modifying sandy soil using the high impermeability curing agent is as follows: adjusting the water content of the sandy soil, uniformly mixing the high impermeability curing agent and the sandy soil at a mass ratio of 5-15:85-95 to obtain a mixed soil material; and preparing test pieces with the mixed soil material.

8. The method for preparing a high impermeability curing agent for sandy soil according to claim 7, characterized in that: When the sandy soil is modified, the moisture content of the sandy soil is 8%-20%.

9. The method for preparing a high impermeability curing agent for sandy soil according to claim 7, characterized in that: The mass ratio of high impermeability solidifying agent to sandy soil is 7-12:87-92.

10. The method for preparing a high impermeability curing agent for sandy soil according to claim 9, characterized in that: The mass ratio of high impermeability solidifying agent to sandy soil is 10:90.

Citation Information

Patent Citations

  • Solid-waste-based high-iron sulphoaluminate maritime work cementing material as well as preparation method and application thereof

    CN113698117A

  • Solid waste source high-activity powder base slurry and preparation method thereof

    CN116947429A

  • High-performance and low-energy-consumption solid waste-based light thermal insulation material and preparation method thereof

    CN118598629A

  • Conductive cement composition having excellent soiladhesion and hardened material constructed from thecomposition

    KR1020010064830A

  • Sulfur-aluminum-iron cement, preparation method therefor, system thereof, and use thereof in marine engineering material

    WO2022142136A1

Cited By

  • Roadbed soil cement cementing material curing agent and use method thereof

    CN120081637A

  • Light UHPC-based logistics tray and preparation method thereof

    CN120535263A

  • Energy storage battery box based on light high-performance concrete and preparation method of energy storage battery box

    CN120864846A